Kako motivirati zaposlene ? - Kušar, Andreja (Revija za univerzalno odličnost, 2014)
Research Question (RQ) : How to motivate employees and keep th em motivated ? Purpose: The purpose of this study is to find out what motivates employees and what motivates employees for work. Method: The results of the questionnaire are graphically presented and described. Random sampling was utilized that included pa rticipants from various professional areas and demographic characteristics. The results showed a relationship between individual motivational factors related to education, age and type of employment. All of the questions were closed - type questions except f or the last question, which was an open question, in which the respondents answered in their own words. Questions were analyzed using frequency analysis of individual responses. Pearson's Chi - squared test, Spearman's rank correlation and Fisher%s Exact tes t was made using R Commander. Results: The research findings showed which motivational factors motivate employees the most. These are especially non - material motivational factors, such as good relationships, jobs with challenges, advancement opportunities, clear instructions, good work conditions, company reputation, etc. Organization: The study will help managers understand their role in motivating employees as well as the types of motivational factors . Society: The research shows how individuals are moti vated . Originality: Certain motivators in the study are ranked differently than was found in previous literature. Most probably the reason is that the respondents in this study favored intangible motivators ( good relations with leadership and their colleag ues , good working conditions, etc. ). Limitations/Future Research : The limitation of this study was that the sample included employees of different ages , gender and years of service in various organizations . To enhance the study and to find similar results as in previous literature, more questions should have been asked as well as increasing the sample size.
Keywords: dejavniki motiviranja; employee; factors of motivation; motivacija; motivation; motivatorji; motivators; organizacija; organization; satisfaction; zadovoljstvo; zaposleni